Respon Pekerja Terhadap Tanggung Jawab Sosial PTPN XII (Persero) Gunung Gumitir Perspektif Kesejahteraan Islam; Studi Etnometodologi - Huwaidi, M Hibatullah (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to find out how the response of the working community at PTPN 12 Gunung Gumitir to corporate sosial responsibility is in accordance with the mandate of the law through TJSL (Sosial and Environmental Responsibility) to pay attention to the welfare level of the surrounding community. With the Ethnomethodology approach it is possible to capture how the working community responds at PTPN 12 Gunung Gumitir. The results of this study indicate that companies are still not maximally carrying out their sosial responsibilities so that the public tends to respond negatively. The community feels boredom due to companies that run without paying attention to the wishes of their workers.